Study Of High Performance Concrete Using Local Materials (Fly Ash Of Pltu Labuhan Angin, Mount Sinabung Volcanic Ash And Silica Sand) On The Mechanical Properties Of Concrete (Talenta Publisher, 2023)
Currently in Indonesia a lot of construction work and concrete is one that is widely used. In the development of concrete construction technology, especially in Indonesia, it is necessary to have concrete capable of carrying high loads using available materials. The development of high quality concrete has 3 levels, namely High Strength Concrete (HSC), High Performance Concrete (HPC) and Ultra High Performance Concrete (UHPC). Against the background of future needs, in this study experiments were carried out in a concrete laboratory to obtain high performance concrete mixes with local materials. At the experimental stage, testing of tools and materials, concrete mix, casting, slump test, manufacture of specimens, maintenance, checking of unit weight, compressive strength test, split tensile strength and modulus of elasticity was carried out. In that study there were 11 variations. Furthermore, the test results were analyzed by the data to draw conclusions. The results showed that the average compressive strength of concrete at 3 days of age was relatively high, namely 53.8 MPa which could be used for fast precision work. In variation 11 mixture (PCC Cement, Silica Fume, Sand Mesh 35-60, Silica Mesh 325, Water, Viscocrete Superplasticizer 8670 MN, Fly Ash 7% and Polypropylene Fiber 0.2%) tested for 28 days, the compressive strength reached 87.5 MPa, so it can be said as HPC concrete. In this study it was concluded that the use of local materials, Sinabung Volcanic Ash waste and fly ash can improve the quality of concrete and can also reduce environmental pollution.